EFEK GEL EKSTRAK ETANOL DAUN ASAM JAWA (Tamarindus indica L.) SEBAGAI PENYEMBUHAN LUKA INSISI PADA TIKUS JANTAN GALUR Sprague Dawley - Agustina Susilowati; Nanda Syta Nur’aini (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2020)
The skin is the outermost organ that protects the body from external damage and can experience injury. Tamarind leaves have several benefits, one of the properties is as a wound healer. This research using 25 male rats Sprague Dawley strain divided into 5 groups. The group consisted of a negative control (base gel), a positive control (comersial gel), an extract of tamarind leaves gel concentration 0.5%, 1%, and 2%. Gel application was carried out 3 times daily as much as 0.2 g for 5 days at the same hour by observing the length of the wound and scab formation. The results showed that the scab appeared on the 3rd day of the early stage of the proliferation process. Extract gel of tamarind leaves with a concentration of 0.5%, 1% and 2% had activity as an incision wound healing until day 5 showed the percentage of incision wound healing reached 17%, 19.8% and 25%. The main efficacious chemical compound for wound healing are flavonoids, saponins and tannins. Based on these results, it can be concluded that concentration extract of tamarind leaves gel the most effective as an incision wound healer is 2% with a wound healing percentage reaching 25%.